Early experiences with saving energy in direct interconnection networks - Zahn, Felix; Lammel, Steffen; Fröning, Holger (Proceedings, 2017)
Energy is emerging to become one of the most crucial factors in design decisions for future large scale computing systems. Especially Exascale-installations will have to operate within hard power and energy constraints. Besides economical reasons, power consumption is also limited by a limited power distribution, cooling capabilities, and minimization of carbon footprints. While other components, such as processors, become more and more energy-proportional, interconnects are still highly energy-disproportional. Although interconnection networks are contributing only about 10-20% to the overall power consumption of High-Performance Computing (HPC) or Cloud systems, this fraction is likely to increase significantly in the near future. Therefore, power saving strategies are mandatory for improving energy efficiency and thereby performance within hard power constraints. In this work, we introduce a simple energy saving strategy, which switches links on and off, depending on the user's performance constraints. Therefore, we adapted an existing OMNeT++ network simulator by adding new energy features. This simulator allows us to run traces of real world applications, including LULESH, NAMD, and Graph500 with different configurations. We show that this policy enables possible energy savings of up to 39% in interconnection networks. Furthermore, we demonstrate the impact of hardware design parameters, such as transition time, on possible power saving strategies.
Gesehen am 03.08.2017
Keywords: Konferenzschrift